Citizen engagement in public food procurement, a novel choose-your-own-adventure canteen campaign case study - Luke John Schafer; Anna Gundorph; Carla Mingolla; Christian Bugge Henriksen; Marin Lysak; Reni Todorova Boncheva; Maarten Crivits (Social Sciences and Humanities Open)
The Great Food Transformation towards a sustainable food system is urgently needed to address the planetary impacts of consumption and ensure the availability of healthy, affordable, and tasty food for the future. Transforming food systems requires widespread societal shifts and interdisciplinary collaboration on a large scale. Public Food Procurement provides an opportunity to drive systemic change by prioritsing local, nutritious, and sustainable food purchasing on an institutional level. Citizen engagement is an often-overlooked tool that can facilitate food system change with its participatory approaches leading to distributed learning and decentralised knowledge generation. Together with key stakeholders, this study combines both Public Food Procurement practices with citizen engagement strategies to facilitate the transformation to more sustainable food in local canteens at the University of Copenhagen. Existing in-person canteen user-group workshops were re-purposed and coupled with an adapted online survey designed in a ‘Choose-Your-Own-Adventure' style. This approach embedded the FoodSHIFT Citizen Empowerment Scheme, merging interactive engagement with flexible digital participation to enhance user input. The Choose-Your-Own-Adventure Canteen Campaign successfully engaged citizens in the Public Food Procurement process with 94% of respondents reaching the second of four engagement levels by being consulted on their food preferences. A further 24% expressed interest and 10% reached the third level by being involved in workshops. Nine individuals showed signs of reaching the forth and highest-level, empowerment, by expressing their interest in directly improving or collaborating future iterations of the canteen campaign. This transdisciplinary, multi-actor collaboration has demonstrated a simple yet effective survey adaptation that can engage citizen while simultaneously collecting food preference data to inform Public Food Procurement decisions. Although this proof-of-concept study is small in scope, its potential impact is significant. Public Food Procurement and Citizen Engagement are underexplored areas, and combining them into a mutually beneficial approach could amplify transformative change towards Sustainable Food Systems.